ORGANIZATIONAL JUSTICE DAN ORGANIZATIONAL MISBEHAVIOR PADA TENAGA PENJUALAN - Arina, Nidya Ayu; Jayanti, Aldila Dwi; Yulianti, Praptini (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2019)
The purpose of this study was to examine the effect of organizational injustice on organization misbehavior carried out by salespeople because working as a salesperson is full of targets with pressure experienced certainly has high potential for misbehavior. Salespeople are required to achieve the target and not infrequently justify any means to meet the target. Some Previous studies found that organizational injustice can be a trigger for workers to do misbehavior actions. Then the phenomenon arises, whether someone's reasons justify their misbehavior. This research used moral justification which is a process in which an individual carries out deviant actions but the process of action seems morally justified because it seems to have a noble goal. This research was conducted on 150 sales people at 3 consumer goods companies in Surabaya Indonesia and to test statistics,Smart PLS is used. This research is expected to be an input for policy makers to reducing misbehavior and also contributes to research on organizational misbehavior. The results of this study indicate that organizational injustice has a significant effecton organization misbehavior. In addition, moral justification can mediate the influence of both variable